Faktor-Faktor Yang Mempengaruhi Angka Gizi Buruk Pada Balita Di Sumatera Barat Menggunakan Metode All Possible Regression Dari Regresi Linier - Putri, Nurlailatika; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2023)
Currently in Indonesia., health problems are in the spotlight is the high mortality rate in children aged 0-59 month. This problem is caused by malnutrition thar occurs in children in this age group. Solving the problem of malnutrition is a serious challenge in West Sumatra Province which is influenced by various factors that play a role in the problem. This research aims to .determine what are the causes of malnutrition in the West Sumatra region. The approach used is the All Possible Regression method of linear regression, taking into account .factors such as toddlers with low birth weight (x1), exclusive breastfeeding (x2), vitamin A suplemetation (x3), and antenatal visits to pregnant women (x4). According to the research results, a multiple linear regression model has been obtained to identify factors that have an influence on malnutrition rates in toddlesr in West Sumatra as follows: y = 3,95 - 0,0406 x4So, antenatal visits to pregnant women (x4) have a significant effect on the incidence malnutrition in toddlers in West Sumatra with a level of error 5%.